SA-3 Haemogram Parameter of 17 Dogs That Have Been Infected by Ehrlichia canis in My Vets Animal Clinic Kemang in 2017 - Tri Ayu Kristianty; Ni Nengah Yogiswari Resyana (Hemera Zoa, 2018)
Ehrlichiosis is a canine vector-borne disease transmitted by ticks. It is caused by a gram-negative obligate intracellular bacteria of the genus Ehrlichia. Ehrlichia has three different species that can cause canine ehrlichiosis: E. canis, E. chaffeensis, and E. ewingii.Ehrlichia canis causes canine monocytic ehrlichiosis (CME) that is also known as tropical canine pancytopenia, canine rickettsiosis or canine hemorraghic fever. Primary vectors of E. canis are Rhipicephalus sanguineus and Dermacentor variabilis. CME is characterized by three stages, acute, subclinical, and chronic that can be difficult to definitively distinguish in practice.E. canis form microcolonies within a membrane-lined intracellular vacuole that is also called morula, primarily in monocytes and machrophages of mammalian hosts. The patogen replicates only in cytoplasm of monocytic cells and the formation of morulae is defining characteristic that can be used for diagnosis.A case ehrlichiosis in canine can be diagnosed based on clinical signs, blood smear examination, cell culture, serology test, or molecular detection by polymerase chain reaction (PCR).